Обобщенная модель системы формирования процессов и технологий повышения эффективности добычи, переработки и использования углеводородных энергоносителей - Кравченко, О. В. (НТУ "ХПИ", 2008)
Based on the large systems philosophy, a generalised model has been devised for a system of forming processes and technologies to increase the effectiveness of extracting, processing and using hydrocarbon energy carriers. The base components of the generalised model are processes for intensifying extraction, the processing technology, and the technology of using hydrocarbon energy carriers. The generalised model of the system for forming processes and technologies for energy conversion allowed to conduct a theoretical analysis of methods of increasing the effectiveness of the industrial processes of intensifying extraction, processing and using hydro-carbon energy carriers, as well as to develop apparatuses and devices for the implementation thereof.
Keywords: углеводородные энергоносители; гидрокавитационная обработка; суспензионные горючие